Platelets, haemostasis and inflammation - Zirlik, Andreas; Bode, Christoph; Gawaz, Meinrad (Springer, 2017)
The book depicts the various roles of platelets in a variety of cardio-metabolic diseases. Traditional and non-traditional platelet functions are described in detail in atherosclerosis, metabolic syndrome, diabetes, myocardial infarction, and other vascular pathologies. Particular focus is put on platelets as a link between haemostasis and inflammation contributing to both. Last but not least the books links the most recent advances in basic sciences with promising novel therapeutic applications and first results of clinical trials. The book is written for biomedical scientists in the sub disciplines vascular biology, biochemistry and immunology; and it as well will be of interest and value for academic physicians like cardiologists, hematologists, general internists and vascular surgeons.
Keywords: Blood platelets.; Hemostasis.; Inflammation.; Heart -- Diseases.; elektronické knihy; electronic books